Selective screening for inborn errors of metabolism using tandem mass spectrometry in West Kazakhstan children: study protocol - Zharmakhanova, Gulmira; Kononets, Victoria; Balmagambetova, Saule; Syrlybayeva, Lyazzat; Nurbaulina, Eleonora; Zhussupova, Zhanna; Sakhanova, Svetlana; Ayaganov, Dinmukhamed; Kim, Svetlana; Zhumalina, Akmaral (Frontiers in Genetics, 2024)
Data on the prevalence of most inborn errors of metabolism are still unavailable in Kazakhstan. The study aims to perform selective screening for hereditary metabolic diseases among patients aged from 1 day to 18 years in western Kazakhstan using the LC-MS/MS method, with establishing the reference values for the content of amino acids, acylcarnitines, and succinylacetone in blood samples of healthy children. Tasks: 1. To assess the burden of metabolic disorders detected by LC-MS/MS in western Kazakhstan by examination of children at clinical risk in pediatric clinics throughout the region; https://www.frontiersin.org/register?returnUrl=https://loop.frontiersin.org 2. To set the reference values of metabolites in the child population; 3. To analyze the age distribution, prevalence, and age of onset for each identified IEM, further comparing the obtained findings with those from previously published reports in other populations. Methods: To set the reference values of 51 metabolites in the child population, 750 healthy children will be included. The selective screening will be performed among 1,500 patients aged 1 day to 18 years with suspected hereditary metabolic disorders. Anticipated results: The results of selective screening will be interpreted by comparison with the reference values established. Diagnosis will be based on clinical signs, blood levels of amino acids, acylcarnitines, succinylacetone, and urine levels of organic acids and tests for gene mutations. An assessment of 37 inborn errors of metabolism frequencies in high-risk children will be performed. The research will further develop the national as selective as expanded newborn screening programs. The study was registered in clinicaltrials. gov (https://www.clinicaltrials.gov/study/NCT05910151) on 16 June 2023.